Project-Based Learning Model and Its implementation: Students’ Perception in Curriculum Development Subject - Anggaira, Aria Septi (Journal of Education Research, 2022)
This research was conducted to determine students perception about the implementation of project-based learning in the Curriculum Development course. Researcher developed questionnaires as a data collection tool. The respondents in this study were IAIN Metro students in the English study program who were attending curriculum development courses. The results of the questionnaire showed that most students had a positive perception of the implementation of project-based learning. They agree that the material using project-based learning is clear, engaging, and easy to understand. In addition, the use of project-based learning models in curriculum development learning activities can increase their learning motivation. In addition, students have a positive perception of the lecturers' ability to guide and facilitate them in project-based learning